A low-threshold sleep intervention for improving sleep quality and well-being - Eigl, Esther-Sevil; Urban-Ferreira, Laura Krystin; Schabus, Manuel (Frontiers in Psychiatry, 2023)
Background. About one-third of the healthy population is suffering from sleep problems, but only a small proportion of those affected receive professional help. Therefore, there is an urgent need for easily accessible, affordable, and efficacious sleep interventions. Objective. A randomized controlled study was conducted to investigate the effectiveness of a low-threshold sleep intervention consisting either of i) sleep data feedback plus sleep edu-cation, or ii) sleep data feedback alone and in comparison to iii) no intervention. Material and Methods. One hundred employees of the University of Salzburg (age 39.51±11.43, range: 22-62) were randomly assigned to one of the three groups. During the two-week study-period, objective sleep parameters were assessed via actigraphy. In addition, an online questionnaire and a daily digital diary were used to record subjective sleep parame-ters, work-related factors as well as mood and well-being. After one week, a personal ap-pointment was conducted with participants of both experimental group 1 (EG1) and experi-mental group 2 (EG2). While the EG2 only received feedback about their sleep data from week 1, the EG1 additionally received a 45-minute sleep education intervention, containing sleep hygiene rules and recommendations regarding stimulus control. A waiting list control group (CG) did not receive any feedback until the end of the study. Results. Results indicate positive effects on sleep and well-being following a minimal inter-vention with a single in-person appointment including sleep data feedback over the course of 2 weeks. Improvements are seen in sleep quality, mood, vitality, actigraphy-measured sleep efficiency (EG1) and in addition in well-being and sleep onset latency in EG2. The inactive CG, did not improve in any parameter. Conclusions. Results suggest small and beneficial effects on sleep and well-being in people being continuously monitored and receiving (actigraphy-based) sleep feedback when paired with a single-time personal intervention.